Rice body formation due to Haemophilus parainfluenza-associated chronic arthropathy. (2021) - Bhat, Pavan; Khurana, Sahiba; Fanaroff, Rachel; Adams, Scott M.; Rabinowitz, Ronald P.
Abstract: A 68-year-old woman with a medical history significant for psoriatic arthritis was found to have an enlarged, painful lump on her left hip 15 months after intramedullary rod placement for a left subtrochanteric femur fracture sustained in a fall. Histopathological findings showed rice body formation (RBF) with concurrent H. parainfluenza . RBF is a relatively rare arthropathy of a subset of chronic inflammatory disease such as rheumatoid arthritis or tuberculous arthropathy. RBF associated with psoriatic arthritis or orthopedic hardware placement has been reported in a handful of cases in the literature but there has not been any definitive evidence for RBF as a result of Haemophilus parainfluenza infections and is a rather unusual characteristic of this case.